Tinjauan Sistematis Senyawa Metabolit Bioaktif Buah Pepaya (Carica papaya L.) Karakterisasi Kimia dan Aplikasinya dalam Bidang Kesehatan - Khusnul Khotimah Rijie; Ardi Mustakim (Lembaga Pengembangan Kinerja Dosen, 2026)
Papaya fruit (Carica papaya L.) is a tropical plant widely consumed as food and known to contain various bioactive metabolites with potential health benefits. The increasing interest in natural products as functional resources highlights the importance of reviewing the chemical characterization and health applications of papaya bioactive compounds. This article aims to systematically review the types of bioactive metabolites found in papaya fruit, the chemical characterization methods applied, and their potential applications in the health sector. This review was conducted through a literature study of relevant scientific articles, focusing on metabolite identification and biological activity evaluation. The results indicate that papaya fruit contains diverse bioactive metabolites, including flavonoids, phenolic compounds, alkaloids, saponins, terpenoids, and proteolytic enzymes. These compounds are commonly characterized using chromatographic and spectroscopic techniques. Several studies have reported that papaya bioactive metabolites exhibit biological activities such as antioxidant, antimicrobial, anti-inflammatory, and antidiabetic effects. This review suggests that papaya fruit has promising potential as a functional natural resource for health and pharmaceutical applications.